YAP mediates human decidualization of the uterine endometrial stromal cells. (May 2017) - Chen, Hengxi; Song, Yong; Yang, Shiyuan; Fu, Jing; Feng, Xue; Huang, Wei
Abstract: Introduction: The decidualization of uterine endometrial stromal cells (ESCs) is critical for the successful establishment and maintenance of pregnancy and involves extensive cell proliferation and differentiation. A newly established signaling pathway, the Hippo/Yes-associated protein (YAP) pathway, plays a critical role in these proliferation processes. Our previous study demonstrated that YAP is expressed in human ESCs. However, its role in decidualization remains unclear. The objective of the present study was to explore the role of YAP in the decidualization of human ESCs. Methods: The expression of YAP was first investigated in the endometrium of non-pregnant women and in the decidua of pregnant women. The role of YAP was investigated by transfecting ESCs with mRNA silencing constructs and observing the negative effects of this action upon decidualization induced in vitro . Results: Our results revealed that the expression of YAP was higher in decidual cells from early pregnant decidua compared with ESCs from non-pregnant endometrium. The expression levels of YAP and TEA domain 1 (TEAD1) were both increased in ESCs during in vitro decidualization and the knockdown of YAP in ESCs caused negative effects upon decidualization in vitro . Discussion: Our study suggests that YAP is upregulated in human decidual cells compared with ESCs and influences the decidualization of ESCs. Highlights: Expression of YAP in decidual cells is increased compared with ESCs. Expression of YAP and TEAD1 are increased in ESCs during in vitro decidualization. Knockdown of YAP in ESCs deters in vitro decidualization.